Programming logic formulation - Farrell, Joyce (Singapore : Thomson Learning Asia, 2008)
This text provides beginning programmers with a guide to development structured program logic. The book's main goal is to introduce universal programming concepts while enforcing good style and logical thinking along the way.
An overview of computers and logic -- Understanding structure -- The program planning process: documentation and design -- Making decisions -- Looping -- Arrays -- Using methods -- Control breaks -- Solving difficult structuring problems -- Creating print charts -- Understanding numbering systems and computer codes -- Using a large decision table -- Software testing and data validation.
Includes index.
Keywords: LOGIC PROGRAMMING